Breast Cancer Mortality in Young Women in Brazil - Silva, Juliana Dalcin Donini E.; de Oliveira, Rosana Rosseto; da Silva, Mariana Teixeira; Carvalho, Maria Dalva de Barros; Pedroso, Raissa Bocchi; Pelloso, Sandra Marisa (Frontiers in Oncology, 2021)
Objective Malignant breast cancer is the leading cause of death by cancer in young women. The study aimed to determine if breast cancer mortality among young women has increased between the period from 1996 to 2017 in Brazil. Methods A time-series analysis of breast cancer mortality rate in young women (20–39 years old) was carried out. Mortality data, from 1996 to 2017, were collected from the Mortality Information System of the Health Ministry, and demographic data, from the Brazilian Institute of Geography and Statistics. Trends in mortality were performed by Joinpoint Regression, the spatial distribution of the mortality rate was done with the QGIZ Software version 2.18, and Spearman’s correlation coefficient was used to correlate the mortality rates with the Human Development Index. Results There was an increase in breast cancer mortality rates in young women in the majority of Brazilian states, with an upward trend in all regions. The correlation with the Municipal Human Development Index, income, and education had a significant impact on the mortality rate for women from 30–39 years old in both time frames evaluated and for women from 20–29 years old, only from 1996 to 2000. Conclusion The data obtained in the study, showed that even though the breast cancer mortality rate of young women is lower than women over 40 years old, it has been increasing in all regions of Brazil, mostly for women from 30–39 years old, suggesting that this group should be included in screening programs.